Absence of subharmonic response in vibrated granular systems under microgravity conditions - Kollmer, Jonathan; Tupy, Martin; Heckel, Michael; Sack, Achim; Pöschel, Thorsten (Physical Review Applied, 2015)
By means of experiments in microgravity conditions, we show that granular systems subjected to sinusoidal vibrations respond either by harmonic or gaslike dynamics, depending on the parameters of the vibration, amplitude and frequency, and the container size, while subharmonic response is unstable, except for extreme material properties and particular initial conditions. The absence of subharmonic response in vibrated granular systems implies that granular dampeners cannot reveal higher-order resonances, which makes them even more attractive for technical applications. Extensive molecular dynamics simulations support our findings.